PERLINDUNGAN HUKUM BAGI KORBAN PENYEBARAN DATA PRIBADI OLEH PELAKU DEBT COLLETOR PINJAMAN ONLINE - Pramudita, Amanda Cahaya (Universitas Labuhanbatu, 2025)
The dissemination of personal data by online loan debt collectors poses a serious threat to individual privacy rights in the digital era. This research aims to analyze the legal protection for victims as well as the effectiveness of applicable regulations in Indonesia. Using a normative juridical method and a statutory approach, this research examines the legal rules that protect personal data and the obstacles to their implementation. The results show that although regulations such as the Electronic Information and Transaction Law and Financial Services Authority regulations have been implemented, weak law enforcement and low public awareness are the main obstacles. Therefore, it is necessary to strengthen regulations, increase the effectiveness of supervision, and educate the public. This study contributes to the development of personal data protection policies in the digital financial sector and provides a basis for more comprehensive protection efforts.Keywords: Personal Data; Legal Protection; Online Loans; Debt Collector